Pendidikan yang Memanusiakan: Penerapan Mindfulness Dalam Bimbingan dan Konseling Terhadap Resilensi Siswa: Humanizing Educational: Application of Mindfulness in Guidance and Counseling on Student Resilience - Tina, Andi Septiana Syaba; Aswar, Aswar (TARBIYAH: Jurnal Pendidikan dan Pembelajaran, 2025)
Students face various academic pressures and developmental challenges, such as physical, psychological, and social changes, which can negatively impact their emotional well-being. The inability to manage stress can affect academic performance and mental health. One effective approach to enhance resilience and emotion regulation is mindfulness. This article aims to analyze the implementation of mindfulness in guidance and counseling as a strategy to improve student resilience. The research method used is a descriptive qualitative approach, with data collected from secondary sources. The findings indicate that mindfulness can help students develop self-awareness, manage negative emotions, and improve focus in learning. Despite its proven benefits, the application of mindfulness in Indonesian schools is still limited and not systematic. Therefore, specialized training for school counselors, as well as support from the school environment and community, is essential. Mindfulness, as a humanistic approach, should be integrated into the education system to foster emotionally and mentally resilient students.